Retrieving the offspring and caring for it during the first night at home - Castillo Espitia, Edelmira; Ocampo González, Melva Patricia (Investigación y Educación en Enfermería, 2013)
Objective. To describe experiences of mothers caring for their preterm offspring on the first day after being discharged from the hospital. Methodology. This was an interpretative phenomenological study with 10 mothers. Results. Release of the infant from the hospital was interpreted by the mothers as an event that permits them to retrieve the offspring that did not belong to them but to the hospital personnel. The experience of caring for the child during the first night at home was undertaken with uneasiness, angst, and total dedication. Conclusion. After the child's hospitalization, the mothers doubt their own capacity to care for it. It is necessary to implement strategies that permit mothers to know their offspring and participate in the care during the hospitalization to build trust in their capacity to care for the child at home.